LANGUAGE OF SCIENCE: A DISCUSSION PAPER - Mustafa Kamal Nasution (Jurnal As-Salam, 2017)
In Indonesia, the issue of scientific language has never been discussed and tend to be ignored by any educators. The content of this paper attempts to relate challenges and issues in the recent scientific language to the Indonesian education system. Here, English is a foreign or second language. Analysing the language of science in English, hence, is challenging since it has two steps of difficulties; interpreting the scientific languages to English first, and to Bahasa afterwards. Hopefully, portraying those challenges would widen the clarity of the recent language of science issues and contribute to a valuable outcome in the Indonesian science education context, and lastly arouse any further action in science education development.